Oral Cancer and HPV: Review Article - Pirmoradi, Zahra; Nazari, Kasra; Shafiee, Nadia; Nikoukar, Nikou; Minoo, Shima; Ghasemi, Hadis; Ghanbarikondori, Parizad; Allahyartorkaman, Mohammadreza (Asian Pacific Journal of Cancer Biology, 2024)
Overview: Oral cancer poses a significant global health challenge, with approximately 300,000 new cases reported annually. Human papillomavirus (HPV) has emerged as a major risk factor for the development of oropharyngeal cancer, constituting around 60% of all oral cancer cases. This review aims to present a comprehensive overview of the current relationship between HPV and oral cancer, covering aspects such as epidemiology, clinical features, detection, treatment, and prevention strategies. Methods: A comprehensive literature search was conducted using Web of Science, PubMed, and Scopus databases to identify studies published in English from January 1983 to the present that investigated the association between HPV and oral cancer. Relevant articles were selected based on their applicability to the topic and methodological quality. Results: The literature search yielded 115 studies that met our inclusion criteria. Our analysis revealed that HPV is a common finding in oral cancer, with a pooled prevalence rate of 72.8%. HPV-positive oral cancer is associated with younger age at diagnosis, male gender, lower stage at presentation, and better prognosis compared to HPV-negative tumors. The HPV genotype most commonly detected in oral cancer is HPV-16, followed by HPV-18. Conclusion: HPV significantly contributes to the onset of oropharyngeal cancer, and identifying it early can serve as a valuable indicator for diagnosis and prognosis. More investigation is required to grasp the molecular mechanisms involved in HPV-related oral cancer and to formulate successful prevention and treatment approaches. Immunization against HPV, particularly in young males, shows potential for decreasing the occurrence of oral cancer linked to HPV.